Analysis of Nursing Service Quality Based on Servqual and Al-Islam Kemuhammadiyahan Values as Determinants of BPJS Patient Loyalty - Nova Rita; Linda Handayuni; Sri Nova Deltu; Mandria Yundelfa; Farisa Anggela (Postgraduate, University of Mataram, 2025)
The National Health Insurance (JKN) program encourages hospitals to improve service quality to maintain patient loyalty, particularly among BPJS patients. Nursing services play a pivotal role in patient interaction, while the integration of Al-Islam Kemuhammadiyahan (AIK) values is believed to strengthen the spiritual dimension of care. This study aims to analyze the effect of nursing service quality based on SERVQUAL (Tangibles, Reliability, Responsiveness, Assurance, Empathy) and AIK values on BPJS patient loyalty at RSU Aisyiyah Padang. A quantitative cross-sectional design was employed, involving 120 inpatient BPJS participants selected through consecutive sampling. Data were collected using SERVQUAL questionnaires and AIK-based instruments. Data analysis included univariate, bivariate (Chi-Square test), and multivariate (logistic regression) analyses. The results show that the majority of patients were female (54.2%) with senior high school (37.5%) and university education (29.2%). The highest-rated SERVQUAL dimension was Empathy (74.2%), while Tangibles remained the lowest (53.3%). Most patients rated the implementation of AIK values as good (73.8%) and were categorized as loyal (77.5%). Bivariate analysis indicated that all SERVQUAL dimensions and AIK values were significantly associated with patient loyalty (p < 0.05). Multivariate analysis revealed that only Assurance (p = 0.010; Exp(B) = 0.223) and AIK values (p = 0.000; Exp(B) = 0.93) significantly influenced patient loyalty. These findings confirm that nurse competence, assurance, and the application of Islamic values are dominant factors in fostering BPJS patient loyalty. This study provides a basis for developing hospital policies that integrate service quality and Islamic values.